Study of Morphology and Morphometry of Placenta - Ch. Sudhakarbabu; M. Indira (Academia Anatomica International, 2020)
Introduction: The placental examination provide significant information related to intrauterine foetal death, Intrauterine Growth Retardation, Malformations, infections and effects of maternal diseases on fetal growth. The magnitude of the clinical problems related to the development and the functions of the placenta is so vast that it worth undertaking morphological aspect of Human placenta A thorough examination of the placenta is neglected often underestimated by the Physician and Gynecologist Pediatrician and pathologist despite its invaluable role in the fetal development. Subjects and Methods: In our present study, 50 freshly delivered placentae have collected The placenta and the umbilical cord were examined to look for any abnormalities in the shape, cord insertion, and vessels in the cord, placenta weight, its circumference, diameter, volume, and thickness at the level of cord insertion were also noted. Baby's weight at birth and age in weeks, maternal history about diabetes and hypertension were also recorded down. IBM SPSS Statistics for Windows version 20.0, USA was used to do statistical analysis of the measurements. Results: In the present study, the placenta weight, volume, diameter, and circumference show a strong correlation with fetal weight. We found the placenta of round and abnormal shapes in 88% and 12% of cases, respectively. In 77% of cases, we got normal cord insertion and in 23% of cases, abnormal cord insertion. Statistical analysis of all the parameters of the placenta was done. Conclusion: In our study, Placental weight, volume, diameter, and circumference showed a strong correlation with fetal weight. The knowledge of these measurements on the placenta and umbilical cord will be helpful to the pediatrician and obstetrician in clinical practice.